Connectivity and Functional Specialization in the Brain 2021
DOI: 10.5772/intechopen.95614
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profile as a Marker of Cell Damage and Immune Dysfunction after Spinal Cord Injury

Abstract: The study reviews findings of the recent experiments designed to investigate cytokine profile after a spinal cord injury. The role of key cytokines was assessed in the formation of cellular response to trauma. The specific immunopathogenic interaction of the nervous and immune systems in the immediate and chronic post-traumatic periods is summarized. The practicality of a step-by-step approach to assessing the cytokine profile in spinal cord injury is shown, the need to take into account the combination of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…The study of specific immune subsets obtained from the peripheral blood of patients with chronic SCI has received increasing attention in recent years. Along these lines, previous works have identified altered levels of multiple serum cytokines and immune populations in patients with SCI [ 16 , 17 ]. For instance, we showed that enhanced markers of intestinal barrier dysfunction and inflammatory markers such as tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) can be observed in patients with chronic SCI, which are associated with impaired function of circulating monocyte [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of specific immune subsets obtained from the peripheral blood of patients with chronic SCI has received increasing attention in recent years. Along these lines, previous works have identified altered levels of multiple serum cytokines and immune populations in patients with SCI [ 16 , 17 ]. For instance, we showed that enhanced markers of intestinal barrier dysfunction and inflammatory markers such as tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6) can be observed in patients with chronic SCI, which are associated with impaired function of circulating monocyte [ 18 ].…”
Section: Introductionmentioning
confidence: 99%